The language advantage: how multilingualism shapes our minds - Hayitmurodova Gulinur Zafarovna (International Journal Of Literature And Languages, 2025)
This article gives information about multilingualism – the use of several languages within a certain social unit, how to become one of multilingual people and the benefits of learning and using two or more languages for the personal and professional development. It also explains a profound contribution of multilingualism to cognition, to the brain, to success and wellbeing across the entire lifespan.